TECHNO-ECONOMIC OF HYDROGEN PRODUCTION WITH BRINE UTILIZATION TECHNOLOGY AT ULUBELU GEOTHERMAL POWER PLANT - Mochammd Resha (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Indonesia's substantial geothermal potential, particularly at the Ulubelu Geothermal Working Area, offers a strategic opportunity for green hydrogen production by utilizing brine energy that is currently reinjected into wells. This study aims to analyze the techno-economic feasibility of an integrated hydrogen production system at Ulubelu Geothermal Power Plant Units 3 and 4, utilizing Thermoelectric Generator (TEG), Organic Rankine Cycle (ORC), and a combined TEG+ORC configuration to convert brine thermal energy into electricity for powering a Proton Exchange Membrane Electrolyzer (PEME) with a capacity of 1000 kg/day. The methodology includes thermodynamic modeling based on mass, energy, and exergy balance under steady-state conditions, as well as economic investment analysis encompassing Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Levelized Cost of Hydrogen (LCoH) under two electricity price scenarios (0.075 USD/kWh and 0.126 USD/kWh). The results show that cooling tower and PACWP modifications successfully provide 102.94 kg/s of cooling water per unit with an additional power consumption of 88 kW, reducing cooling water temperature from 38.8°C to 28°C and increasing cooling tower exergy efficiency from 94.92% to 98.22%. The PEM electrolyzer system achieves an energy efficiency of 86.6% and an exergy efficiency of 3.4%, producing 1079 kg H₂/day and 8628 kg O₂/day. Economically, the ORC configuration consistently delivers the best performance, with the lowest LCoH of 4.16 USD/kg (at 0.126 USD/kWh) and 5.06 USD/kg (at 0.075 USD/kWh), the highest IRR of 15.51% – 20.31%, and the fastest payback period of 6 – 7 years. In contrast, the TEG+ORC combination yields the highest LCoH (6.9 – 7.73 USD/kg) and the longest payback period (9 – 11 years). It is concluded that the ORC-based brine-to-hydrogen system is the most techno-economically viable option for hydrogen production at the Ulubelu Geothermal Power Plant.